Nonpharmacological treatments for Tourette syndrome and tic disorders: A protocol for systematic review and network meta-analysis. Issue 19 (14th May 2021) - Suh, Hyo-Weon; Kwon, Chan-Young; Hong, Sunggyu; Lee, Hyun Woo; Lee, Misun; Kim, Jong Woo; Chung, Sun-Yong
Abstract: Background: A tic is a sudden, rapid, recurrent, nonrhythmic motor movement, or vocalization. Tic disorders are diagnosed based on the presence of motor or vocal tics, duration of tic symptoms, and age at onset. Current clinical practice guidelines strongly recommend behavioral therapies because they are more effective and safer than medications. To determine the most effective nonpharmacological intervention for tic disorders and Tourette syndrome, we will conduct a systematic review and network meta-analysis. Methods: We will search the Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, PsycARTICLES, AMED, 3 Chinese databases (China National Knowledge Infrastructure, Chongqing VIP, and Wanfang Data), 3 Korean databases (Korean Medical Database, Korean studies Information Service System, and ScienceON), and a Japanese database (CiNii). There will be no language or date restrictions. The primary outcome will be the tic severity scale, the Yale Global Tic Severity Scale. The secondary outcomes will include the effective rate defined by the trial authors, dropout rate, and adverse events. Methodological quality will be assessed using the Cochrane risk of bias tool. Results: Results of this review and network meta-analysis will be published in a peer-reviewed journal. Conclusions: This systematic review will assess the effectiveness of nonpharmacological interventions for treating tic disorders. A systematic review or meta-analysis will provide an unbiased overview of the existing evidence. Abstract : Supplemental Digital Content is available in the text